Cameron‐Liebler line classes in PG(3, 5). Issue 12 (24th October 2018) - Gavrilyuk, Alexander L.; Matkin, Ilia
Abstract: We complete a classification of Cameron‐Liebler line classes in PG ( 3, 5 ) and show in a uniform way all nonexistence results for those in PG ( 3, q ), q ≤ 5 .